Literacy, Numeracy, and Digital Practices at Home Among NEET Individuals in Germany : How are They Associated with Future Work and School? - Pullman, Ashley [Verfasser]; Krejcik, Luise [Verfasser] (Beltz Juventa, 2021)
"For adults who are not in education, employment, or training (NEET), an important source of their informal learning is literacy, numeracy, and digital (LND) practices at home. By analyzing data from the Programme for the International Assessment of Adult Competencies (PIAAC) and the longitudinal follow-ups in Germany, this study provides insight into the literacy, numeracy, and problem solving in technology-rich environments skill profile of NEET individuals and examines if LND activities at home contribute to their level of skill in these areas. Additional longitudinal analysis examines the association between the probability of being NEET two and four years later and initial level of LND activities at home. Together, the results demonstrate that literacy, numeracy, and problem-solving skills are lower among NEET individuals and LND activities partially account for their difference in average skill levels compared to non-NEET people. Over time, LND activities at home have a small association with a lower probability of being NEET two years later but minimal to no association four years later." (Authors' abstract, BIBB-Doku)

"Für Erwachsene mit NEET-Status (not in employment, education, or training) sind literale, numerale und digitale (LND) Praktiken zu Hause wichtige Formen des informellen Lernens. Diese Studie bietet - basierend auf Daten des Programme for the International Assessment of Adult Competencies (PIAAC) und der weiteren Langzeitstudie PIAAC-Longitudinal (PIAAC-L) - Einblicke in des Kompetenzprofil von NEET-Personen in Deutschland und analysiert, ob LND-Aktivitäten zu Hause ihre Testergebnisse in standardisierten Kompetenztests beeinflussen. Eine zusätzliche Längsschnittanalyse untersucht den Zusammenhang zwischen dem vorangegangenen LND-Aktivitätsniveau und der Wahrscheinlichkeit zwei und vier Jahre später NEET zu werden. Insgesamt zeigen die Ergebnisse, dass die Kompetenzen im Bereich Numeralität, Literalität und Problemlösung bei NEET-Personen im Vergleich zu Nicht-NEET-Personen geringer sind. Der Unterschied im durchschnittlichen Kompetenzniveau liegt partiell in den LND-Aktivitäten begründet." (Autorenreferat, BIBB-Doku)
Keywords: P 1.2 Erwachsene; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; L 2.1.1 Informelles Lernen; L 6.2.1 Standards/Gütekriterien; 370; Erwachsener; Arbeitsloser; Jugendlicher ohne Ausbildungsvertrag; Informelles Lernen; Lesen; Schreiben; Mediennutzung; Kompetenzbewertung; Langzeitstudie; PIAAC